Pentingnya Pendaftaran Tanah untuk Memastikan Kepemilikan yang Sah - Bahmid Bahmid; Pratiwi, Irda; Rahmadi, Yudha; Putri Putri; Hadi, Neil Falah; Suherman, Luthfi Fahreza (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2025)
Land is a valuable asset with high economic, social, and legal significance. Legal certainty over land ownership is crucial to preventing disputes, facilitating transactions, and supporting economic development. However, many people in Indonesia have yet to officially register their land, including those in Sei Kamah Baru Village, Asahan Regency. The main factors contributing to this issue are the lack of public understanding of land registration procedures, the perception of high costs, and the minimal outreach from relevant authorities. This community service activity aims to raise awareness and understanding among the public about the importance of land registration to ensure legal ownership. The methods used in this program include preparation, legal counseling sessions, discussions, and administrative assistance for residents who wish to process their land certificates. The counseling session was held on January 30, 2025, at the Sei Kamah Baru Village Hall, attended by local residents, village officials, and representatives from the National Land Agency. The results of this activity indicate an increase in public awareness regarding the importance of land certification and its registration procedures. Additionally, some residents have taken the initiative to process their land certificates after receiving assistance from the community service team. This counseling session had a positive impact on enhancing legal awareness and encouraging land ownership legalization to prevent future disputes. For the program's sustainability, more intensive counseling sessions and collaboration with the government and the National Land Agency are needed to simplify the land registration process for the community.